Mampu Mengakhiri Pembelajaran - Cinta Rusmauli Simanjuntak (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
Education involves a complex process consisting of interactions between teachers, students, and the learning environment. The ability to complete learning is an important indicator of the success of the education system in conveying understanding and skills to students. This research is intended to investigate the factors that influence students' ability to complete learning well. The research method applied involves secondary data analysis from several related studies, surveys, and interviews with teachers and students. The research results show that elements such as teaching methods, student motivation, parental support, and availability of learning resources have a central role in the ability to complete learning. The use of innovative and student-focused teaching methods has proven successful in increasing students' understanding and interest in learning. Student motivation, whether it originates from the student or is stimulated by the teacher, has a positive impact on student learning efforts. Parental support and the availability of adequate learning resources also contribute to creating a supportive learning environment. In addition to these factors, this research highlights the importance of a holistic approach to learning, where students' emotional, social and psychological aspects are considered in a balanced manner. Therefore, the ability to complete learning includes not only academic achievement, but also the development of relevant life skills. The results of this research contribute to our understanding of how to improve the education system to be more effective in helping students achieve optimal learning completion abilities. Practical implications of this research involve expanding innovative teaching approaches, increasing parental support, and increasing access to learning resources. Thus, learning is not only a process, but also an achievement that has a positive impact on students' lives in the long term.